2xy+6h=

Simple and best practice solution for 2xy+6h= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2xy+6h= equation:


Simplifying
2xy + 6h = 0

Reorder the terms:
6h + 2xy = 0

Solving
6h + 2xy = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2xy' to each side of the equation.
6h + 2xy + -2xy = 0 + -2xy

Combine like terms: 2xy + -2xy = 0
6h + 0 = 0 + -2xy
6h = 0 + -2xy
Remove the zero:
6h = -2xy

Divide each side by '6'.
h = -0.3333333333xy

Simplifying
h = -0.3333333333xy

See similar equations:

| (2x-3)/6 | | 17=18-1b | | (10x-3y)-(8y+1)= | | -3+-18r=-345 | | 5x^2+6y+1=0 | | 3(1+6r)=-87 | | 4x+2x+56=180 | | -(2-3p)=p-18 | | 36=8z+20 | | 7/8*2 | | .291666= | | 0.03p+0.05(1300-p)=75 | | 3/x-3×5/2x-6=11/2 | | 3/9=y/12 | | (X+1+2i)(x+1+2i)=0 | | -3r+8+5r+-1= | | 5+2z=2z+6 | | 15x+5=10x | | 5x-3=-9x-7 | | 5+3(5)-(4)(5)= | | w/6=4/8 | | 50x-125= | | 4/3*3.14*7.4 | | 10+x=5(15x+2) | | 10x=15x+5 | | 1/3=-3/5u-1/2 | | 9s-1/3=3/2/3 | | 13=-1/6TH | | x^2+9x-25=0 | | 7x+4-6x=15-20 | | -0.18t=5.2 | | 2x-5=3x-1.50 |

Equations solver categories